Seroprevalence of neutralizing antibodies against human adenovirus type 55 in the South Korean military, 2018-2019. - So Yun Park; Jae-Hoon Ko; Sezim Monoldorova; Jonguk Jeong; Bo-Young Jeon; Soon-Hwan Kwon (PLoS ONE, 2020)
We conducted a seroprevalence study of a large ongoing outbreak of human adenovirus type 55 (HAdV-55) among the military in South Korea. Serum samples were collected between 2018 and 2019 from military-exposed (military group) and non-exposed (non-military group) populations. The plaque reduction neutralization test (PRNT) was used to assess neutralization activity against HAdV-55. A total of 100 sera was collected from the non-military group, of which 18.8% showed HAdV-55 neutralizing antibody activity. Ninety-six sera were tested from the military group, which had significantly higher prevalence of neutralizing antibodies (56.0%, P <0.001). A significantly higher proportion of the military group had PRNT titers ≥1:1,000 than the non-military group (85.7% vs. 50.0%, P = 0.004). Among the military group, 48.9% of active-duty soldiers had PRNT titers ≥1:5,000, while none of the discharged civilians did (P = 0.007). In conclusion, Koreans were exposed to HAdV-55 in their communities, but the exposure risk was higher among people in military service.